Alternative procedure of sales comparison method in valuing property - Abdul Rahman, Rohana (2013)
The Sales Comparison Method (SCM) is the most widely used method of property valuation; particularly for residential properties. With transaction data becoming more and more accessible, the trend of using Comparison Method will continue; the valuation of commercial properties is expected to also use this method. However, SCM is criticised for its subjectivity with inconsistent prediction; SCM procedure relies too much on the expert judgment of the valuer such that the value of property varies between valuers. This paper puts forward a proposal for an alternative technique using SCM that will minimise subjectivity in property value prediction with reduced complexity. The aim of this research is to develop a formal automated procedure of the Sale Comparison Method for double storey terrace house. The conceptual procedure was developed by examining peer research, Malaysian Valuation Standard, a standard in use throughout the Valuation and Property Services Department in Malaysia. The research uses this conceptualisation to examine the extent to which a formal procedure can be developed for double storey terrace. Taman Daya and Bandar Mahkota Cheras were chosen due to substantive data in that locality. The conceptualisation translated into an alternative technique follows three steps of property valuation. For the comparable selection, Minkowski metric is used for selecting the best comparable, then Ordinary Least Square (OLS) regression model is used for adjustment of the comparable and lastly weighting strategies for comparable reconciliation. Seven years data of double storey terrace houses is empirically tested using the alternative procedure and it is found that for 10% estimation range the accuracy of valuation is between 51% and 93% while for 20% estimation range the accuracy of valuation is between 76% and 97%. The finding satisfied the 10% acceptable range specified by the technical circular of the Valuation Department therefore the result obtained proved that the proposed procedure can be accepted for single valuation purposes. The proposed technique closely resembles the existing procedure to gain the confidence of valuers; however, tasks that require judgments from valuers are substituted with statistical methods. This technique avoids the often criticised complexities of the new SCM variants. Integration of this formal implementation with Geographic Information System (GIS) resulted of an automated valuation model (AVM). AVM is more accurate and less human bias also can reduce cost of operation and can realized quick valuation compared to valuation exercised manually.